(untitled) (Религиски дијалог и соработка, 2025)
This study aims to analyze three key dimensions: the historical-cultural approach, theological interpretations, sociological analyses, and narratives, with a particular emphasis on the Old Testament and gender asymmetry in the creation myth, as well as the Apostle Paul’s teachings on women. The historical-cultural approach seeks to investigate the historical foundations of gender roles within Christianity and the various interpretations that have shaped societal attitudes and norms concerning gender. Additionally, this research will examine the manifestations of gender within Christian communities, particularly the status of women in the Christian tradition and the role of Christianity in shaping and reinforcing gender stereotypes. This involves an exploration of gender dynamics across different Christian denominations, highlighting both progressive and conservative perspectives. Furthermore, this study will address women’s activism and the role of feminist theology, commonly referred to as Christian feminism, within Christian communities. It will examine contemporary challenges faced by women in their efforts to resist patriarchal traditions and explore potential avenues for transforming patriarchal structures within religious institutions. Ultimately, this research aims to assess the broader impact of the Christian tradition on modern society and its influence on religious and cultural frameworks from a gendered perspective.